DESIGNING AN IMPROVED SERVICE DELIVERY FRAMEWORK IN TRANSPORT DEPARTMENT BASED ON STRATEGIC DETERMINANTS THROUGH QFD - S.V.R. Murty; V.V.S. Kesava Rao (Utilitas Mathematica, 2025)
The prioritized service delivery dimensions in the transport department – namely Licensing and User Accessibility, Support and Compliance Services, Safety and Emergency Management, Penalty Management, and Public Awareness – were strategically mapped to five modern service design pillars to identify actionable improvement areas. These pillars include User Experience, Feedback & Response Mechanisms, Technology Infusion (AI, IoT, Automation), Environmental Sustainability, and Service Resilience. This alignment forms the foundation of a Quality Function Deployment (QFD) framework, facilitating the translation of user-centric needs into Design and operational solutions. The resulting matrix provides a structured mechanism for evaluating how each dimension can be strengthened through appropriate technological, managerial, and environmental strategies.